Ekokritik dan Estetika ʿArūḍ dalam puisi Nasionalisme Ali Ahmad Bakatsir - Aulia Fitriani; Minatur Rokhim (Institut Muslim Cendekia, 2026)
Ecocritical studies in modern Arabic literature remain relatively limited, particularly those integrating environmental representation with the aesthetics of Arabic prosody (ʿArūḍ). Meanwhile, the nationalist poetry of Ali Ahmad Bakatsir not only expresses patriotic ideals but also portrays nature as an essential element in constructing national identity and poetic meaning. This study aims to examine the relationship between ecocentric messages and the musical aesthetics in Ilā Indūnīsiyā al-Bāsilah by Ali Ahmad Bakatsir. This research employed a qualitative approach using a textual analysis method. The analysis was conducted based on Lawrence Buell's ecocriticism and the theory of Arabic prosody (ʿArūḍ), while the data were collected through observation and note-taking techniques. The findings reveal that nationalism in Bakatsir's poem is constructed through a harmonious relationship between humans, nature, and spiritual values. Nature is represented as an active entity possessing intrinsic value and contributing to the formation of national identity. There are four verses that meet Lawrence Buell's ecocriticism criteria out of a total of twelve verses, namely meeting the criteria; first, the non-human environment, second, human interests do not exceed other legitimate interests, third, human responsibility towards the environment, fourth, the environment is understood as a dynamic process. Among them, there are phrases mountains, plains, pearls, the eastern end, gardens and the Qur'an that meet the first criterion of Lawrence Buell's ecocriticism non-human environment. From the aesthetic aspect, the poem uses Baḥar Roml which is dominated by the fāʿilātun pattern with several variations of ziḥāf in the form of khobn, which makes taf'ilah which turns into fa'ilatun, thus producing a strong, heroic, and authoritative rhythm.